THE PHILOSOPHICAL FOUNDATION OF THE SCHOOL LITERACY MOVEMENT IN INDONESIA - Nandy Intan Kurnia (Jurnal Pendidikan, 2021)
The School Literacy Movement (SLM) was launched in 2015 by the Indonesian government in response to the concerns of many parties regarding the readiness of the Indonesian young generation to face the challenges of the 21st-century. This paper examined the philosophical foundations of SLM by scrutinizing the School Literacy Movement Master Design published in 2019 as the object of study. This study was a descriptive qualitative study, using the inferential content analysis method. The findings were: (1) the philosophical foundation of SLM that is portrayed in the object of study are essentialism, perennialism, progressivism, existentialism, and critical pedagogy, and (2) the object of the study is strongly influenced by the philosophy of progressivism since the writers of the SLM Master Design were more focused on the effort to prepare the students to face the 21st-century challenges. Gerakan Literasi Sekolah (GLS) atau The School Literacy Movement (SLM) atau dicanangkan pada tahun 2015 oleh pemerintah Indonesia, sebagai jawaban atas keprihatinan banyak pihak terkait kesiapan generasi muda Indonesia menghadapi tantangan abad 21. Tulisan ini mengkaji landasan filosofis SLM dengan menelaah Desain Induk Gerakan Literasi Sekolah terbitan 2019 sebagai objek kajian. Penelitian ini adalah penelitian deskriptif kualitatif yang menggunakan metode analisis isi inferensial. Temuan penelitian adalah: (1) Landasan filosofis SLM yang tergambar dalam objek kajian adalah esensialisme, perenialisme, progresivisme, eksistensialisme, dan pedagogi kritis; dan (2) Objek kajian sangat dipengaruhi oleh filosofi progresivisme karena penulis Desain Induk SLM lebih fokus pada upaya mempersiapkan siswa untuk menghadapi tantangan abad ke-21.